Autoantibodies and fecal calprotectin levels in a group of Colombian patients with inflammatory bowel disease (2020)
Background: The purpose of the study is to investigate the frequency of serum anti-Saccharomyces cerevisiae antibodies (ASCA), anti-neutrophil cytoplasmic antibodies (ANCA), anti-nuclear antibodies (ANAS), IgA, C reactive protein (CRP), erythrocyte sedimentation rate (ESR) and fecal calprotectin (FC) and its association between diagnosis, endoscopic findings, histopathologic and clinical activity, in patients with diagnosis or suspected inflammatory bowel disease (IBD). Methods: An observational cross-section study was designed including 52 patients with IBD or suspected IBD. ASCA, ANCA, ANAS, IgA, CRP, ESR and FC were measured. Patients were divided according to histological findings into ulcerative colitis (UC), Crohn's disease (CD) and others (normal mucosa, chronic proctocolitis, nonspecific colitis and ileitis). A descriptive analysis was made and associations were evaluated using chi2 test, Kruskal Wallis and Mann- Whitney U test. Results: The association between IBD and ASCA levels was statistically significant (p=0.036). ANCA levels showed statistical significance in IBD patients (p=0.048). When comparing FC levels within UC, CD and others a statistical significance was obtained (p=0.032). A large percentage of patients (78.5%) with high positive levels FC were classified as active histopathology. A significant percentage (54.5%) with levels up to 50 mg/kg had quiescent activity. Positive levels of FC were related with serum activity markers with statistical significance (CRP: p=0.007 and ESR: p=0.003). Conclusions: The frequencies of p-ANCA and ASCAs for UC and CD were established in a Colombian population. IBD patients with histopathologic activity had higher levels of FC. We also found that patients with quiescent disease have elevated FC levels.